PREDICTION OF FREQUENCY OF INSURANCE RISK BASED ON STOCHASTIC MATRIX AND INAR(1) POISSON MODEL - Haryanto, Dwi
One of the risks that might occur in insurance companies is the decrease in income from customer premiums. The decrease in income is due to the frequency of coming out customers is greater than the frequency of new customers (registering). Therefore, it is necessary to control the pattern of changes in customer behavior to minimize risk. In this thesis, time prediction is made on costumer loyalty and prediction of the possibility of reduced customer frequency. Prediction of time of customer loyalty is constructed using stochastic matrices. Meanwhile, prediction of the possibility of reduced customer frequency is constructed using INAR(1) Poisson model. The result obtained is insurance companies need to provide special treatment to customers who have reached a certain period of premium payments. This is intended to maintain customer loyalty so that the risk from reduced customer frequency can be minimized.